TATA CARA DAN UPACARA SEPUTAR DAUR HIDUP MASYARAKAT JAWA DALAM SERAT TATACARA - Ekowati, Venny Indria (Diksi, 2015)
This article is about a research study conducted to describe the life-cycle manners and rituals according to a classical Javanese text titled Serat Tatacara (or ST, for short) written by Ki and Nyai Padmasusastra in 1863-1904. The text, which was the subject under study, was in prose and published by Kangjeng Gupremen in st Batawi in 1907 in 2 volumes, the 1 of which containing 22 chapters covering 80 nd pages and the 2 containing 18 chapters covering 105 pages. The content is presented in the form of dialogues or question-and-answer sessions between family members. The research data were compiled by careful and direct reading on the subject. The instruments used for data compilation were data sheets. The data were analyzed by using a descriptive analysis technique practiced in such research. The result of the research is a description of the life-cycle manners and rituals implied in ST, which, on the basis of the research result, are grouped into 3 phases: (1) the part covering the prenatal phase contains information about recognizing signs of pregnancy, what are forbidden and what are recommended during pregnancy, the ritual feast held when the pregnancy is 1 and 9 months old, and the manners practiced during childbirth, (2) the part covering the postnatal phase contains information about how to sever the placenta and what to do with it, how to take care of the mother and the baby after childbirth, and the postnatal rituals from brokohan, held right after childbirth, to slametan nyapih, held at the time the infant ceases being breastfed, and (3) the part covering childhood and adolescence contains information about the rituals of tetesan (the female counterpart of circumcision), pasah (the leveling of the horizontal edge of teeth), sukeran (banishment of bad luck), sunatan (circumcision), and tingalan (letting a girl be seen by visiting prospective parents-in-law) and the manners practiced by parents to find a spouse for their son or daughter. Keywords: manners and rituals, life cycle, Serat Tatacara